2020
DOI: 10.1016/j.jcis.2019.12.108
|View full text |Cite
|
Sign up to set email alerts
|

Role of interfacial elasticity for the rheological properties of saponin-stabilized emulsions

Abstract: HypothesisSaponins are natural surfactants which can provide highly viscoelastic interfaces. This property can be used to quantify precisely the effect of interfacial dilatational elasticity on the various rheological properties of bulk emulsions. ExperimentsWe measured the interfacial dilatational elasticity of adsorption layers from four saponins (Quillaja, Escin, Berry, Tea) adsorbed on hexadecane-water and sunflower oil-water interfaces. In parallel, the rheological properties under steady and oscillatory … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 78 publications
(116 reference statements)
0
25
0
Order By: Relevance
“…From the experimental results described so far we can conclude that the high shear elasticity of Yucca-stabilized emulsions, prepared with non-purified oil, is related to the presence of phytosterols in the oily phase which interact with the saponins from the aqueous phase and form elastic skin on the drop surface. However, as showed in our previous study (Tsibranska et al, 2020) the high interfacial elasticity (per se) can increase the shear elasticity of bulk emulsion by up to 4 times, as compared to the elasticity of emulsions with fluid adsorption layers. On the other hand, in the current study we found that the emulsion elasticity increased by ca.…”
Section: Origin Of the Extremely High Elasticity Of Emulsions Stabilmentioning
confidence: 55%
See 2 more Smart Citations
“…From the experimental results described so far we can conclude that the high shear elasticity of Yucca-stabilized emulsions, prepared with non-purified oil, is related to the presence of phytosterols in the oily phase which interact with the saponins from the aqueous phase and form elastic skin on the drop surface. However, as showed in our previous study (Tsibranska et al, 2020) the high interfacial elasticity (per se) can increase the shear elasticity of bulk emulsion by up to 4 times, as compared to the elasticity of emulsions with fluid adsorption layers. On the other hand, in the current study we found that the emulsion elasticity increased by ca.…”
Section: Origin Of the Extremely High Elasticity Of Emulsions Stabilmentioning
confidence: 55%
“…an order of magnitude lower, at Φ SFO = 75 vol. % (Tsibranska et al, 2020). Another reference worthy to note is the elasticity of hexadecane emulsions, stabilized by Quillaja saponin extract QD with very high interfacial elasticity, which was ≈ 800 Pa at 75 vol %, whereas the FD-stabilized emulsions have emulsion elasticity of 4000 Pa at the same Φ SFO .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Different studies with various saponins groups have indicated the ability of these compounds to improve the emulsions' characteristics. Saponins increase the stability of emulsions containing crude oil [13], pure hydrocarbons such as hexadecane, and natural oils including sunflower oil [14], rice bran oil [15] and olive oil [16]. It was also found that the presence of saponins led to a significant decrease in emulsion droplet size; however, the saponins' impact on the droplets' zeta potential was ambivalent [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Even higher foam elastic modulus and yield stress values, not captured by the correlation between foam and interfacial viscoelastic properties, were found under conditions favoring protein aggregation and were attributed to lamellae spanning structures. Tsibranska et al 10 suggested the bulk elastic modulus of emulsions to scale with interfacial dilatational elastic modulus E A 4 5 mN m À1 as follows:…”
Section: Introductionmentioning
confidence: 99%